Detection and partial characterization of an isolate of Groundnut ringspot virus in Solanum sessiliflorum - BOARI,ALESSANDRA J. (2002)
The cubiu (Solanum sessiliflorum) fruit, originating in the Amazon basin, is commonly used in that region for food, medicine, and cosmetics. In an experimental culture of cubiu, in order to evaluate its adaptation to conditions in the Northern region of the state of Rio de Janeiro, it was observed plants with mosaic symptoms. A cubiu plant was collected and analyzed to identify the etiological agent. After mechanical passage through a local lesion host, a host range test was performed. The virus induced chlorotic local lesions in Chenopodium quinoa, necrotic local lesions in Gomphrena globosa, mosaic in S. sessiliflorum, leaf and stem necrosis in tomato (Lycopersicon esculentum) 'Rutgers', mosaic and leaf distortion in Datura stramonium and Physalis floridana, and necrotic local lesions followed by systemic necrosis and plant death in four Nicotiana species. Electron microscopic observations of ultra thin sections from infected cubiu leaves showed the presence of spheroidal, membrane-bound particles typical of tospovirus species. Analysis of the nucleocapsid protein from concentrated virus particles indicated the presence of a 28 kDa protein. RT-PCR was performed after total RNA extraction from infected IPA-6 tomato leaves. A fragment of approximately 0,8 kbp corresponding to the N gene was amplified, cloned and sequenced. The N protein from the cubiu isolate was 95% homologous to the Groundnut ringspot virus (GRSV) protein, and no more than 85% homologous to those from Zucchini lethal chlorosis virus (ZLCV) and Chrysanthemun stem necrosis virus (CSNV), Tomato spotted wilt virus (TSWV), and Tomato chlorotic spot virus (TCSV). This is the first report of the occurrence of GRSV (or any other plant virus) in cubiu.